An Empowerment Model of Counsellor Education - Hawley McWhirter, Ellen (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of this article is to apply an empowerment model of counselling to counsellor education programs, describing how the critical components of empowerment can be infused into counsellor education curriculum.